Reforming the Greek Pension System - Kangur, Alvar (IMF Working Papers; Working Paper ;, 2021)
The Greek pension system has been costly, complex, and distortive, which has contributed to Greece's fiscal problems and discouraged labor force participation. Several attempts to reform the system faltered due to lack of implementation, pushback by vested interests, and court rulings leading to reversals. A series of reforms introduced throughout 2015-17 unified benefit and contribution rules, removed several distortions and reduced fragmentation and costs. If fully implemented throughout the long-term, these reforms can go a long way towards enhancing the pension system affordability. However, reforms faced setbacks and fell short of creating stronger incentives to build long contribution histories, to deliver sustainable growth by improving the fiscal policy mix, and to ensure fairness and equitable burden sharing across generations and interest groups. Policy priorities should aim towards fully implementing the 2015-17 reforms and complementing them with additional reforms to address these remaining objectives.